2015
DOI: 10.1364/ao.54.002501
|View full text |Cite
|
Sign up to set email alerts
|

Low threshold Er_xYb(Y)_2−xSiO_5 nanowire waveguide amplifier

Abstract: The 1.53 μm gain characteristics of ErxYb(Y)2-xSiO5 nanowire and film material waveguide amplifiers have been investigated considering the upconversion effect by solving rate equations and propagation equations. The gains of ErxYb(Y)2-xSiO5 nanowire waveguides have a significant enhancement compared with those of film material waveguides due to low propagation loss and long photoluminescence lifetime. The cooperative upconversion (CUC) effect pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…21 Later, impressive progress has been made since the fabrication of Si− Er 3 (SiO 4 ) 2 Cl core−shell nanowires for Si-compatible light emission in 2011. 26 In the past decade, a variety of monocrystalline RE silicate nanowires [e.g., Er 3 (SiO 4 ) 2 Cl, 14−16 Si(Er x Yb 1−x ) 2 Si 2 O 7 , 18 Er x Yb(Y) 2−x SiO 5 , 17 and Er−Y chloride silicate 20 were prepared by a chemical vapor deposition (CVD) for the implementation of giant optical gain, 16 long-lived fluorescence, 19 low-threshold waveguide amplifiers, 13 and room-temperature upconversion lasers in the communication wavelength (∼1.53 μm). 20 In this work, we report the synthesis and characterization of a monocrystalline Tb 3 (SiO 4 ) 2 Cl with the shapes of core−shell nanowires and nanotubes by a one-step CVD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Later, impressive progress has been made since the fabrication of Si− Er 3 (SiO 4 ) 2 Cl core−shell nanowires for Si-compatible light emission in 2011. 26 In the past decade, a variety of monocrystalline RE silicate nanowires [e.g., Er 3 (SiO 4 ) 2 Cl, 14−16 Si(Er x Yb 1−x ) 2 Si 2 O 7 , 18 Er x Yb(Y) 2−x SiO 5 , 17 and Er−Y chloride silicate 20 were prepared by a chemical vapor deposition (CVD) for the implementation of giant optical gain, 16 long-lived fluorescence, 19 low-threshold waveguide amplifiers, 13 and room-temperature upconversion lasers in the communication wavelength (∼1.53 μm). 20 In this work, we report the synthesis and characterization of a monocrystalline Tb 3 (SiO 4 ) 2 Cl with the shapes of core−shell nanowires and nanotubes by a one-step CVD.…”
Section: Introductionmentioning
confidence: 99%
“…At present, a variety of RE-doped materials have been extensively studied to extract the characteristic emissions of RE ions. , However, their emission is often significantly quenched at high RE density due to the inevitable ion precipitation induced by the degraded lattice matrix of their host material and the increased cross-relaxation between neighboring RE ions as a result of the reduced ion spacing. , The limited stable RE density in most RE-doped materials has become a major challenge in supporting high optical gain for monolithically integrated photonics and optoelectronics (e.g., optical amplifiers and lasers). As a class of potential materials to address this challenge, monocrystalline RE silicates have attracted particular research interest due to their high RE density without ion precipitation and emission quenching. Furthermore, RE silicates exhibit additional advantages, including a highly symmetric crystal field, excellent chemical/thermal stability, and a low Schottky barrier on n -type silicon. In addition, considering that RE silicates are lattice-matched with monocrystalline silicon and silicon is chemically involved in the formation of RE silicates, the combination of RE silicates and silicon nanostructures would provide exciting opportunities for monolithic integration of photonics with silicon, which has been the subject of active research. Therefore, RE silicate crystals have been proposed for the implementation of modern solid-state phosphors and monolithic lasers. ,,, While RE silicates have been extensively studied for a long time, their low-dimensional nanostructures were less explored. In 2005, Choi et al reported the growth of Si/Silica/Er 2 Si 2 O 7 core–shell nanowire heterostructures with carrier-mediated 1.53 μm Er 3+ luminescence consisting of a series of very sharp peaks .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, interests in EDWAs have been re-aroused in the past decade due to the tremendous breakthroughs in the waveguide manufacturing. Recent years have witnessed that a surge of material platforms could be successfully exploited to achieve EDWAs including lithium niobite, [11][12][13][14] silicon nitride, [15] silica [16] and other metal oxides. [17] Despite the significant breakthroughs, the adopted doping strategies can't apply to other materials featuring low rare-earth ion solubility or low-temperature tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Y 3+ , Yb 3+ ) to reduce the strong interaction between erbium ions. [30][31][32] But these substitution ions make the concen-tration of Er 3+ return to 10 21 cm −3 , which indicates that the LDP is still not high enough due to the loss of the high concentration of erbium ions. Another recent study has reported a high LDP of 1.3 × 10 19 s × cm −3 from the film with erbium silicate nanowires embedded in amorphous silica, improving the luminescence lifetime of erbium ions by altering the phonon density of states effects.…”
Section: Introductionmentioning
confidence: 99%